Regulatory phosphorylation of cyclin-dependent kinase 2: insights from molecular dynamics simulations - Bártová, Iveta; Koca, Jaroslav; Otyepka, Michal (Journal of molecular modeling, 2008)
The structures of fully active cyclin-dependent kinase-2 (CDK2) complexed with ATP and peptide substrate, CDK2 after the catalytic reaction, and CDK2 inhibited by phosphorylation at Thr14/Tyr15 were studied using molecular dynamics (MD) simulations. The structural details of the CDK2 catalytic site and CDK2 substrate binding box were described. Comparison of MD simulations of inhibited complexes of CDK2 was used to help understand the role of inhibitory phosphorylation at Thr14/Tyr15. Phosphorylation at Thr14/Tyr15 causes ATP misalignment for the phosphate-group transfer, changes in the Mg(2+) coordination sphere, and changes in the H-bond network formed by CDK2 catalytic residues (Asp127, Lys129, Asn132). The inhibitory phosphorylation causes the G-loop to shift from the ATP binding site, which leads to opening of the CDK2 substrate binding box, thus probably weakening substrate binding. All these effects explain the decrease in kinase activity observed after inhibitory phosphorylation at Thr14/Tyr15 in the G-loop. Interaction of the peptide substrate, and the phosphorylated peptide product, with CDK2 was also studied and compared. These results broaden hypotheses drawn from our previous MD studies as to why a basic residue (Arg/Lys) is preferred at the P(+2) substrate position.
Keywords: threonin; Cyclin-Dependent Kinase 2; Phosphorylation; Catalytic Domain; cyklin-dependentní kinasa 2; Humans; Protein Structure, Secondary; vazebná místa; lidé; sekundární struktura proteinů; tyrosin; katalytická doména; fosforylace; Tyrosine; Binding Sites; Threonine